From one to two quaternary centers: Ester or nitrile α-alkylation applied to bioactive alkaloids. Issue 52 (27th December 2018) - Voute, Nicholas; Neal, Andrew R.; Medda, Federico; Johnston, Craig A.; Slawin, Alexandra M.Z.; Westwood, Nicholas J.
Abstract: The synthesis of all-carbon quaternary centers remains a challenge. Here we describe studies on the formation of two adjacent all-carbon quaternary centers in the context of the planned synthesis of the bioactive natural products perophoramidine and the communesins. In one approach the key step involves ester-alkylation using either allyl bromide or formaldehyde as the electrophile. An unexpected rapid auto-oxidation reaction during the synthesis of the alkylation substrates limited the scalability of this approach. In a second route, alkylation of a nitrile-containing precursor was planned. The use of the TosMIC reagent on a complex substrate gave the nitrile for alkylation. The assignment of the relative stereochemistry of the products was done through the extensive use of small molecule X-ray crystallography. Graphical abstract: